DISPERSION OF HARMFUL SUBSTANCES DISCHARGE FROM SOURCES OF FOUNDRY SHOPS IN ENVIRONMEN - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The results of dispersion of harmful substances discharge in environment from the sources of casting houses on the enterprise territory, sanitary protection zone and residential community are given.